Uncatalyzed synthesis of thiomorpholide using polyethylene glycol as green reaction media - Gawande, Shrikant S.; Bandgar, Babasaheb P.; Kadam, Prasad D.; Sable, Shailesh S. (Green Chemistry Letters and Reviews, 2010)
Polyethylene glycol-600 was used as an efficient and recyclable solvent for the one-pot three component condensation reactions of aryl alkyl ketones, sulfur, and morpholine to produce the corresponding thiomorpholide. This protocol has advantages of high yields, short reaction times, mild reaction conditions, minimal environmental pollution, and simple work up procedure. [GRAPHICS] .
Keywords: polyethylene glycol-600; Sulfur; thiomorpholide; Willgerodt-Kindler reaction